250 years of disturbance dynamics in a pristine old-growth Picea abies forest in Arkhangelsk region, north-western Russia - Khakimulina, Tatiana (2011)
To describe the historical patterns of natural disturbance regimes in European boreal forests we conducted a dendroecological study in a primeval old-growth spruce dominated stands and reconstructed the long-term dynamics of canopy disturbances. We treated the radial growth releases of individual sub-canopy trees as the major indicator of sudden openings in the forest canopy. Growth releases were detected by using the formal approach only (strict criteria were applied). The reconstruction of past canopy disturbances was done by GIS-based analysis of spatial information on released trees over the study period. The study area was located in the transitional vegetation zone of the middle and northern taiga, on the watershed of Northern Dvina and Pinega rivers, North-Western Russia. Spatial and temporal characteristics of canopy disturbances were studied within the area of 1.8 ha along the two transects, 20x450 m2 each. All trees with DBH > 6 cm (dead and alive) and coarse woody debris (DBH > 18 cm) within transects were mapped and described (n = 2126) and all living and recently dead trees were sampled with an increment corer (n = 1678) at the height 40 cm above the root collar. Stands were composed of Picea abies and Betula pendula, mean standing volume was 211 m3/ha. Spruce was of multiple ages with pronounced regular peaks (cohorts) in trees age distribution. At least four such cohorts were distinguished and represented peaks in spruce regeneration. No evidence of stand replacing events was found over the 250(300)-year period that the study covered. The dynamics was likely driven by small and middle-size canopy disturbances, occurring at varying frequencies. A detailed spatial disturbances reconstruction reflecting the last 170 (160) years revealed a disturbance rate of about 4% yearly mortality. Periodic increases in disturbance rate however played a major role in forest regeneration. Four such peaks were timed to decades 1850, 1890, 1930 (1920 – for transect 1) and 1980. Disturbance rates at peaking ...